Understanding current situations: facilitating inclusive education implementation - Alias, Maizam; Harrington, Ingrid; Paimin, Aini Nazura; Lai, Chee Sern; Lee, Ming Foong; Mohamed, Maziana; Wan Mohamed, Wan Azlinda (American Scientific Publishers, 2016)
This paper aims to highlight the current gaps in practices among Secondary schools teachers who are involved in the Malaysian Special Education Integration Program (SEIP). A one to one interview was conducted on 13 teachers who teach the inclusive classes at one secondary school to identify their individual needs with respect to successfully integrating special needs students into mainstream classrooms. Findings were discussed in relation to several aspects of teaching and learning, including inclusive students’ characteristics, appropriate and inappropriate school based practices, and challenges faced by inclusive teachers. Based on the findings, recommendations are made for school-based improvement and teacher-professional developments that inform policymakers on future development plans.